Preliminary observation of particulate organic carbon (POC) contents in water environment of the downstream of Red River system - Hieu, Vu Huu; Quynh, Le Thi Phuong; Josette, Garnier; Etcheber, Henri; Thuy, Duong Thi; Cuong, Ho Tu (Vietnam Journal of Earth Sciences, 2012)
POC (particulate organic carbon) is one of major forms of organic carbon in water. It plays an important role in assessment of river water quality. The observed results in period from April 2009 to April 2010 at the gauging stations in downstream of the Red River showed that the average concentration of POC of the Red River at Truc Phuong and Hanoi stations were the highest (1.797 and 1.727 mg.l-1, respectively) followed by Nam Dinh station (1.414 mg.l-1), Quyet Chien station (1.329 mg.l-1), and the lowest value (0.904 mg.l-) at the Ba Lat station. The POC concentration at all observed stations showed positive correlation with water discharge and total suspended solids, but the percentage of POC contents in total suspended solids decreased with increasing total suspended solids contents. All that introduced the strong erosion and leaching processes in the watershed and its impacts to the POC content in the Red River system.